The Growth Suppressor PML Represses Transcription by Functionally and Physically Interacting with Histone Deacetylases - Wu, Wen-Shu (American Society for Microbiology, 2001)
The growth suppressor promyelocytic leukemia protein (PML) is disrupted by the chromosomal translocation t(15;17) in acute promyelocytic leukemia (APL). PML plays a key role in multiple pathways of apoptosis and regulates cell cycle progression. The present study demonstrates that PML represses transcription by functionally and physically interacting with histone deacetylase (HDAC). Transcriptional repression mediated by PML can be inhibited by trichostatin A, a specific inhibitor of HDAC. PML coimmunoprecipitates a significant level of HDAC activity in several cell lines. PML is associated with HDAC in vivo and directly interacts with HDAC in vitro. The fusion protein PML-RARα encoded by the t(15;17) breakpoint interacts with HDAC poorly. PML interacts with all three isoforms of HDAC through specific domains, and its expression deacetylates histone H3 in vivo. Together, the results of our study show that PML modulates histone deacetylation and that loss of this function in APL alters chromatin remodeling and gene expression. This event may contribute to the development of leukemia.